Leading police organisations in crises: how changing customary police leadership responses impacts on frontline officers’ senses of ontological security - Leslie, Neil (Policing and society, 2025)
The coronavirus pandemic presented the UK police service with extraordinary and unanticipated challenges. The central role of the police in protecting public health situated frontline officers in unaccustomed territory with citizens, colleagues, and leaders. Incongruence between legislative powers and public health messaging created policy ambiguity for police officers in respect of everyday interactions with citizens, while the pandemic’s social restrictions necessitated intraorganisational adjustments. These included a hugely accelerated expansion of technologically mediated communication, and the ability for officers who did not have public-facing roles to work from home. The changes resulted in modifications to the customary, established, command and control procedure used by the police when responding to critical and crisis situations; the so-called Gold, Silver, Bronze (GSB) structure, which has over the past four decades become the routinised, anticipated organisational response to such situations. In this paper we explore whether the ontological security of frontline officers was undermined by pandemic policing’s disruption to these standardised intraorganisational procedures for leading critical and crisis situations. Using empirical data from a mixed method study within two UK police forces, we examine the issue from the frontline officer perspective. Despite organisationally adopting the normatively anticipated response, the GSB model’s adaptation resulted in reduced volumes of proximal support, communication, and direction from senior leaders, and did not therefore meet frontline officers’ normative expectations of crisis command and leadership, a consequence of which was weakened levels of ontological security within frontline officers. As everyday working practices develop within policing, we propose that the study exposes potential weakness in the GSB structure.